Can carbon be “sequestered” while preserving the biodiversity of forests? Review of scientific evidence and recommendations (UNED Research Journal, 2019)
Tropical forests store a great portion of the terrestrial carbon in their biomass and initiatives such as REDD+ (Reducing Emissions from Deforestation and forest Degradation) aim to avoid the emission of this carbon by protecting forests. Nevertheless, not all carbon-rich forests are also rich in biodiversity. Here, I summarize existing information on the carbon-biodiversity relationship in tropical forests, highlighting the need for REDD+ to explicitly consider biodiversity conservation, not just carbon sequestration.
Keywords: REDD; carbon-biodiversity relationship; tropical forest; soil; mitigation; climate change